Orthodontic Wire Ingestion during Treatment: Reporting a Case and Review the Management of Foreign Body Ingestion or Aspiration (Emergencies) - Mohammad Hoseini; Seyed Morteza Saadat Mostafavi; Navid Rezaei; Ehsan Javadzadeh Boluri (Case Reports in Dentistry)
Today orthodontic treatment is in growing demand and is not limited to a specific age or social group. The nature of orthodontic treatment is such that the orthodontic wires and appliances, which are used to apply force and move the teeth, are exposed to the oral cavity. Shaping and replacing these wires in oral cavity are the major assignments of orthodontist on appointments. Therefore, we can say that orthodontic treatment requires working with dangerous tools in a sensitive place like oral cavity which is the entrance of respiratory and digestive systems. In this paper, a case of ingesting a broken orthodontic wire during eating is reported, and also necessary remedial measures at the time of encountering foreign body ingestion or aspiration are provided.